2017
DOI: 10.4142/jvs.2017.18.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Extensive characterization of feline intra-abdominal adipose-derived mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) isolated from various tissues have been well characterized for therapeutic application to clinical diseases. However, in contrast to MSCs from other animal species, the characteristics of feline MSCs have not been fully documented. In this study, we conducted extensive characterization of feline adipose tissue-derived MSCs (fAD-MSCs). Study fAD-MSCs were individually isolated from the intra-abdominal adipose tissues of six felines. The expression levels of cell surface markers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…These samples also had the slowest P2 doubling time. The range of doubling times reported here are consistent with some previous publications of feline abdominal adipose tissue [28][29][30] but slower than those reported by others [20,31].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These samples also had the slowest P2 doubling time. The range of doubling times reported here are consistent with some previous publications of feline abdominal adipose tissue [28][29][30] but slower than those reported by others [20,31].…”
Section: Discussionsupporting
confidence: 92%
“…However, the presence of Sox2 in feline adipose-derived MSCs is controversial. Some have reported the inability to detect Sox2 or the resulting protein in feline abdominal or subcutaneous adipose MSCs [28,29]. In contrast, our results are consistent with those of Lee et al, showing detection of Sox2 in the abdominal adipose tissue [31].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Challenging the paradigm of the constitutive representation of MSC-markers, research shows that CD105 expression can be controlled by oxygen availability in the cellular micromilieu (Sánches-Elsner et al, 2002; Mark et al, 2013), while CD90 representation on the cell surface can depend on the extent of cell–cell connections (Kim et al, 2017). In both cases, these markers have a negative correlation, respectively, with their above-mentioned parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, adipose-derived MSCs (aMSCs) are most commonly used in clinical applications due to ease of attainment and their superior proliferative ability (Webb et al, 2012). Adipose tissue is usually collected from ventral abdomen just caudal to the umbilicus by 8 mm punch biopsy or peritoneal fat is collected during spay procedure (Kim et al, 2017). Authors previous experience showed that even a small surgical wound might bring a risk of severe complications.…”
Section: Fig 2 Leopard Bm Cells Collected On 22 Ndmentioning
confidence: 99%